Deepening Andre Delbecq's legacy: Inspiring undergraduate students to serve humankind. Issue 1 (1st January 2020) - Le, Long; Mark Fusco, S.J.
ABSTRACT: In the past, the typical business school professional saw little need to even broach the spiritual calling. However, Andre's vocational journey as a scholar-teacher significantly contributed to this change, and many of his colleagues are continuing and looking forward to the possibilities of Andre's work. Through a Jesuit-lay friendship with the second author, the first author began to take Andre's call in integrating business as a noble vocation at the undergraduate business level. In connecting classroom assignments and activities with Andre's scholarship, undergraduate business students were invited to consider what kind of person they would want to be and what kind of world they would want to live in. Here, the article chronicles the work of Andre that inspired changes in the first author's pedagogy toward coursework that embraces the discipline to make profits along with the discipline to be human – crossing geographical, political, cultural and religious boundaries – in order to meet the world's needs.